Valoración docente del potencial de los juegos educativos y su relación con las capacidades creativas de los niños del 6to grado de primaria del área de comunicación en las I.E Urbanas del distrito de Rioja - Araujo Maldonado, Isidro (2010)
This research is development to value the potential of educational games and understand their relationship with the creative skills of children in the sixth grade of elementary school in the area of communication in the urban educational institutions of Rioja' s district. The problem research is evident in the process of teaching learning which becomes the object of study, in the educational institutions of primary education in our context, according the strategies to show creative skills, very little used educational games strategy in the process of teaching - learning currículum different areas of the primary leve!. T o star to solve this problem, we started to know teaching strategies used by the teachers of the primary level education in the process teaching - learning, and evaluate the degree of assessment which these map to the potential of educational games with the objective of understanding the development of the creative skills of pupils in primary education in the urban area of Rioja's district. The present investigation has the main objective of determine the relationship between the level of teaching assessment of the potential educational games and creative skills of children in the sixth grade of elementary school in the area of communication of the educative institutions of the urban area of the district of Rioja in 2009. The contrasted hypothesis was the alternate, it showed that exist a directly proportional relationship between the level of teaching assessment of the potential educational games and creative skills of children in the sixth grade of elementary school in the area of communication of urban education institutions of the district of Rioja in 2009. The results obtained for the application of statistics formula is (Chi square test) for the verification of the hypothesis, obtaining a calculated value of z: = 12,634 and a tabular value z; = 9,48, verifying that the calculated value is greater than the tabular, which allows you to accept the hypothesis value alternates with 95% confidence. At the end the assess of the investigation let us how important is to aplícate the educational games in learning activities carried out daily by teachers in primary education, helping to a development education and auto realized (creative), which not only learning new skills and strategies of work would be valuable, but that the child would ad quire a number of altitudes that will enrich as well, useful to society.